Monarubins A–C from the Marine Shellfish-Associated Fungus Monascus ruber BB5 - Ran, Yan-Qin; Lan, Wen-Jian; Qiu, Yi; Guo, Qi; Feng, Gong-Kan; Deng, Rong; Zhu, Xiao-Feng; Li, Hou-Jin; Dong, Jun (Marine drugs, 2020)
Three new compounds, monarubins A–C (1, 6 and 13), together with ten known compounds, including four alkaloids (2–5), two isocoumarins (7 and 8) and four polyketides (9–12), were isolated from marine shellfish-associated fungus Monascus ruber BB5. The structures were determined on the basis of the 1D and 2D NMR, MS, UV and IR data. The absolute configurations of compounds 3, 6 and 13 were determined by ECD calculations. The NMR data of compounds deoxyhydroxyaspergillic acid (3) and 2-hydroxy-6-(1-hydroxy-1-methylpropyl)-3-sec-buthylpyrazine (4) were first reported. All of the isolated compounds were evaluated for their cytotoxic activities against human nasopharyngeal carcinoma cell lines CNE1, CNE2, SUNE1 and HONE1 and hepatocellular carcinoma cell lines QGY7701 and HepG2. Monarubin B (6) displayed potent cytotoxicities against the cancer cell lines HepG2 and QGY7701 with IC50 values of 1.72 and 0.71 μΜ, respectively; lunatinin (7) showed moderate cytotoxic activities against the cancer cell lines HepG2, QGY7701 and SUNE1 with the IC50 values of 9.60, 7.12 and 28.12 μΜ, respectively.